2021
DOI: 10.1111/rsp3.12387
|View full text |Cite
|
Sign up to set email alerts
|

Voting with your feet or voting for Brexit: The tale of those stuck behind

Abstract: This paper promotes the idea of a culturally‐sensitive Tiebout–Hirschman–Rothschild mechanism underpinning the UK's 2016 Brexit result. Our culture‐based development (CBD) model asserts a trade‐off between two rival types of voting: voting with one's feet or voting in a radical way due to being unable to vote with one's feet, akin to a protest vote. We explore the effects on the Brexit vote of shares of public spending on culture and a particular type of migration dynamic that triggers social closure. Our find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
(93 reference statements)
1
5
0
Order By: Relevance
“…Concerning unemployment, our findings show that people who live in areas with a high unemployment rate are more likely to abstain. This is consistent with the regional science literature, which has shown that people’s perception of the impossibility of social mobility generates a sense of living in a place that is not only “left behind” but in which they are “stuck behind” (Lee et al 2018; Tubadji et al 2021). This perception of living in areas of relative deprivation consequently triggers resentment.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Concerning unemployment, our findings show that people who live in areas with a high unemployment rate are more likely to abstain. This is consistent with the regional science literature, which has shown that people’s perception of the impossibility of social mobility generates a sense of living in a place that is not only “left behind” but in which they are “stuck behind” (Lee et al 2018; Tubadji et al 2021). This perception of living in areas of relative deprivation consequently triggers resentment.…”
Section: Resultssupporting
confidence: 90%
“…However, our results show that in municipalities characterised by a form of lock-in in terms of marginality, and where there has been a decline in public services, abstentionism is higher. It is important to take these path dependence effects into account because opportunities for individuals to be socially or spatially mobile determine voting behaviour (Lee et al 2018; McCann 2020; Tubadji et al 2021). In our study, people that abstained felt disengaged because they knew that voting would not change their destiny, namely, being stuck in a neglected area.…”
Section: Resultsmentioning
confidence: 99%
“…Research has found a correlation between average economic conditions, educational success, and support for Brexit in different regions (Alaimo & Solivetti, 2019;Becker et al, 2017;Goodwin & Heath, 2016;Nurse & Sykes, 2019). For instance, Tubadji et al (2021) highlight the negative correlation between culture-related public spendings and Brexit vote. However, there seems to be relatively large geographical variation in the relationship between deprivation and Brexit vote (Nurse & Sykes, 2019).…”
Section: Direct H2) Neighbourhood-level Deprivation Increases the Lik...mentioning
confidence: 92%
“…Moreover, austerity measures and cuts to public spending can contribute to economic grievances and a sense of being left behind and "stuck behind" (Tubadji et al, 2021). This feeling can be amplified when an entire region is affected, leading to support for radical right views.…”
Section: Regional Deprivationmentioning
confidence: 99%
“…The association between the sentiment of being left behind and other socio‐economic factors in the context of radical voting, such as migration and human capital concentration across space, has been documented for the UK (Tubadji et al, 2021) and the Netherlands (Tubadji et al, 2020). 1 Building on Hirschman and Rothschild’s (1973) and Tiebout (1956)’s models, the main argument of these two papers is that existing deprivation and lack of outmigration triggered (among the autochtonous population) a signalling of increasing perceived deprivation in an increasingly less appealing cultural milieu without opportunity for outward and upward mobility.…”
Section: Literature Reviewmentioning
confidence: 99%